Total phenolic, total flavonoids content and antioxidant activity of Mangifera sp. leaf extracts - Athilah Farhanah Ahmad Fuad (2023)
Mangifera sp. is a versatile plant that was reported to have various bioactivities, however only the fruits have gain popularity due to it sweet flesh and been known worldwide. It has a potential source of flavonoids and carotenoids, which makes them a nutritious functional food to consume. This study focused on determination of the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of the Mangifera sp. leaves extract in different water extraction methods. The TPC and TFC was determined by using Folin-Ciocalteu method and aluminium chloride method respectively while antioxidant activity was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and ferric reducing antioxidant power (FRAP) assay. Soxhlet extraction (SXE) produced the highest extraction yield compared to microwave extraction (MWE). MWE at 8 minutes extract showed the highest TPC (262.13±0.05 mg GAE/g). SXE showed the highest TFC (413.46±0.77 mg rutin/g). The highest antioxidant activity was recorded in MWE 8 minutes extract through DPPH and FRAP assays compared to other two MWE extract and SXE extract.